Proper motion of the spectrally selected structures in Herbig-Haro flows - Movsessian, T. A.; Magakyan, T. Yu.
We present some results of the investigations of proper motions of spectrally separated structures in the Herbig-Haro (HH) outflows with the aid of Fabry-Perot scanning interferometry. This project was started more than twenty years ago on the 2.6m telescope of Byurakan Observatory and afterwards was continued on 6m telescope (Russia). We describe the progress of research in the frames of this project and focus in more detail on the results of the latest observations of HH 83 outflow system. The method of Fabry-Perot scanning interferometry allowed to reveal the morphology of high and low velocity structures not only inside the terminal working surfaces of the jets but also in their internal knots. As the great advance we consider the development of a methodology for measuring proper motions of already separated kinematical structures using observations in two epochs, which made it possible to reveal the physical nature of these structures. Concerning the HH83 collimated outflow it should be noted that our first observations of HH 83 revealed two structures in its working surface with strongly different radial velocities, and the second epoch data allowed to measure their proper motions. The proper motions of these structures are nearly equal, which points that they are physically connected and represents forward and reverse shock regions in the terminal working surface of HH 83.
Keywords: Astronomy